Modern food microbiology - Aneja, K.R (Medtech, 2018)
Food Microbiology, an applied branch of microbiology, is an alive science directly related to human health and longevity having ample job opportunities for food microbiologists. It can be defined as the study of microorganisms and food in relation to food contamination, food spoilage, food poisoning, food preservation, food bioprocessing and food legislation. Modern Food Microbiology is a clearly written textbook with the student in mind belonging to food science, microbiology, biotechnology, public health, nutrition, and dietetics, and veterinary science. The summary and multiple choice questions at the end of each chapter are very useful for a quick revision and recapitulation by the students. This book contains 19 chapters discussing all aspects of food microbiology such as: Scope and historical development of food microbiology Characteristics and sources of microorganisms in food Intrinsic and extrinsic factors influencing the microbial growth in food and hurdle concept Microbial spoilage of specific foods Methods to detect and identify food borne organisms bacteria, fungi, protozoa, helminths and prions Intoxication, infections, toxicoinfections and mycelisms Fermented food products, probiotics and edible mushrooms Preservation of foods by microbial control/removal, and combination of methods Predictive modelling, hazard analysis critical control points and regulatory agencies. This book will serve as a useful text for the undergraduate, postgraduate students in the biological sciences, microbiology, biotechnology and food science as well as a valuable reference for researchers, teachers, industrialists and professionals in food microbiology or food safety.